Microplastic effects in aquatic ecosystems with special reference to fungi–zooplankton interaction: identification of knowledge gaps and prioritization of research needs - Yadav, Devesh Kumar; Kumar, Ram (Frontiers in Ecology and Evolution, 2023)
Microplastics (MPs) are plastic particles ≤5mm in size, that end up ultimately in marine and freshwater ecosystems, adversely affecting various ecological functions. With the multifaceted roles of fungi and their diverse modes of interaction such as saprobic, epibiotic, endobiotic, parasitic, and symbiotic or being a nutritionally enriched food source in aquatic ecosystems, the effect of MPs on fungi-plankton interactions is still less explored. Properties of MPs such as (i) size range similar to those of microeukaryotes, (ii) substrate for unique microbiota, (iii) ability to be transported from the source to faraway waterbodies, and (iv) sorption of pollutants, have adverse effects on various guilds of ecological organization. MPs also tend to alter nutrient cycling and inhibit efficient energy transfer through microbial and mycoloop in an ecosystem. This paper comprehensively reviews the effect of MPs at the population and community level on the complex ecological (fungi-phytoplankton-zooplankton) interactions with an emphasis on the role of fungi in the aquatic ecosystem. Examination of existing literature revealed that MPs can interfere in ecosystem functioning by acting in synergy with fungi, while antagonistically affecting the community and vice -versa. Herein, we explore current understanding of the effect of MPs on major components of microbial and mycoloop in the marine food web, elaborating MPs-mediated changes in the ecosystem functioning, identifying research gaps, and highlighting the need for future research.